2014
DOI: 10.1371/journal.pone.0100786
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Tissue Environment in NEMO-Deficient Mice Critically Regulates Positive Selection of Donor Cells after Hepatocyte Transplantation

Abstract: BackgroundHepatocyte transplantation (HT) is a promising alternative treatment strategy for end-stage liver diseases compared with orthotopic liver transplantation. A limitation for this approach is the low engraftment of donor cells. The deletion of the I-kappa B kinase-regulatory subunit IKKγ/NEMO in hepatocytes prevents nuclear factor (NF)-kB activation and triggers spontaneous liver apoptosis, chronic hepatitis and the development of liver fibrosis and hepatocellular carcinoma. We hypothesized that NEMOΔhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In the canonical pathway, IKKβ is necessary and sufficient for phosphorylation of IκBα, which leads to the activation of NF-κB and associated with prevention of apoptosis, cytokine production and inflammation. The deletion of the IKK-regulatory subunit IKKγ/NEMO in hepatocytes prevents NF-κB activation and triggers spontaneous liver apoptosis, chronic hepatitis and the development of liver fibrosis and hepatocellular carcinoma [ 43 ]. In addition, it has been shown that IKKβ activated NF-κB and induced IL-6 production [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the canonical pathway, IKKβ is necessary and sufficient for phosphorylation of IκBα, which leads to the activation of NF-κB and associated with prevention of apoptosis, cytokine production and inflammation. The deletion of the IKK-regulatory subunit IKKγ/NEMO in hepatocytes prevents NF-κB activation and triggers spontaneous liver apoptosis, chronic hepatitis and the development of liver fibrosis and hepatocellular carcinoma [ 43 ]. In addition, it has been shown that IKKβ activated NF-κB and induced IL-6 production [ 44 ].…”
Section: Discussionmentioning
confidence: 99%